Maternal and Neonatal Outcomes of Pregnancy in Women With Chronic Hypertension: A Retrospective Analysis of a National Register. Issue 4 (December 2016) - Broekhuijsen, K.; Ravelli, A.C.; Langenveld, J.; van Pampus, M.G.; van den Berg, P.P.; Mol, B.W.; Franssen, M.T.
Abstract : ( Acta Obstet Gynecol Scand 2015 ;94(12):1337–1345) Increased risk of adverse pregnancy outcomes (preeclampsia/eclampsia, placental abruption, preterm delivery, growth restriction, and maternal and perinatal mortality) is noted in pregnancies complicated by chronic hypertension. The objective of this study was to assess whether planned early delivery may prevent some of these adverse outcomes. To achieve this objective, maternal and neonatal outcomes of pregnancy in women with chronic hypertension, including gestational-age–specific outcomes were studied.